Effects of social support on vision-related quality of life in older adults with dry eye disease: the chain mediating role of illness perception and coping style - Pan, Haoran; Pan, Xubin; Gu, Danfeng; Wang, Xiaobo (Frontiers in Psychology, 2024)
Objective This study explored the effects of social support, illness perception, coping style, and vision-related quality of life (VRQOL) in older patients with dry eye disease (DED) using a chain mediation model. Methods A total of 407 patients with DED from a tertiary hospital in Wuxi, Jiangsu Province, China, between June and December 2023 were selected as participants. A demographic questionnaire, the Social Support Rating Scale, the Brief Illness Perception Questionnaire, the Medical Coping Modes Questionnaire, and the National Eye Institute Visual Functioning questionnaire-25 were all given to them to complete. IBM SPSS (version 27.0) was used for data analysis, and Model 6 of the PROCESS Macro was used to test the predicted chain mediation model. Results The positive association between social support and VRQOL demonstrated the mediation role of illness perception and coping style. Social support affected VRQOL via three pathways: illness perception (effect = 0.190), confrontational coping style (effect = 0.103), and a combination of illness perception and confrontational coping style (effect = 0.067), accounted for 23.60%, 12.80%, and 8.32% of the total effect, respectively. Conclusion Social support in older patients with DED can significantly and positively predict the VRQOL. In addition to the independent mediating effect of illness perception and confrontational coping style, a chain-mediating effect exists between social support and VRQOL. The study serves as a valuable strategy for healthcare professionals to prevent and intervene in VRQOL for older patients with DED in the future.